(untitled) (Journal of Health, Technology and Science (JHTS), 2024)
Fishermen are among the professions that work at night, so fatigue often occurs. Sleep quality is an important factor for a person’s well-being. Poor sleep quality can cause increased stress, which in turn can increase blood glucose levels. The aims of this study were to determine the description of blood glucose levels in fishermen working at night. This study uses a quantitative approach and descriptive research. The data used are primary in the form of research results and secondary data in the form of data from literature, books, and journals. The sampling technique used was Accidental sampling, assuming the number of samples was 30. The results showed that most respondents had normal glucose levels, namely 18 people (60%) and abnormal 12 people (20%). The elderly category has high blood glucose levels, namely one person, and normal, namely 4, with 5 people. As for adults, high blood glucose levels were 11 and regular 14, with a total of 25 people.